Un confronto possibile: Philippe Buchez e Giuseppe Mazzini - Rosanna Marsala (Laboratoire Italien)
There seems to have been no direct contact between Philippe Buchez, an exponent of French social Catholicism, and the layman Giuseppe Mazzini, but the two likely got to know each other through their work. Although they came from different backgrounds, Buchez was nevertheless a spiritualist, a republican, an ‘anticlerical’, a staunch pro-European and shared with the Genoese a past as a Carbonaro. Both firmly believed that national education must be imparted to all the people who wanted to become men and citizens because, without it, there would be no moral nation. For Buchez, national education ‘doit être obligatoire’. The two also agreed on the principle of nationality. For Buchez, as for Mazzini, nationality is not identified with nationalism, nor can it be restricted to a community of language, history and traditions. It is part of that law of progress that drives all nations to pursue the ‘common purpose of activity’. It cannot be denied, moreover, that Buchez shared with Mazzini the idea of a brotherhood of peoples based on democracy, understood as government freely permitted by all. Given these affinities, and despite the differences, the parallels between two contemporary thinkers who contributed to the development and affirmation of democracy are clear.